A nano-watt power-on reset circuit with Brown-Out detection capability. (November 2020) - Sun, Ting; Yu, Qi; Ning, Ning; Wu, Ke-Jun; Zhang, Zhong; Li, Jing
Abstract: Ultra-low-power microcontrollers play an important role in system applications. In this paper, a Nano-watt Power-On Reset (POR) circuit with Brown-Out Detection (BOD) capability was proposed. The proposed circuit implemented in a 0.18 ​μm CMOS process, which contains long-reset and fast-reset time mode and provides a reset signal with approximately 3.314s and 22 ​ms, respectively. The embedded brown-out detection circuit can detect the event in time, as long as the abnormal supply voltage decreases to 1.4 ​V and the brown-out duration is longer than the microsecond range under 1.8 ​V–3.3 ​V. To further reduce power consumption, a bias state switching circuit and a Vpulse control signal generating circuit are proposed to reduce the static current in the start-up circuit and Schmitt triggers circuit. The circuit consumes less than 100 ​nA under 1.8 ​V–3.3 ​V power supply and occupies 110 ​× ​100 ​μm 2 area.